Learning Style Preferences of Medical Students in Kano, Northwestern, Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Context:The current literature posited that the knowledge of learning styles can be useful to both teachers and students. This study sets out to investigate and compare the learning style preferences of medical students (2ndyear–5thyear).Aims:The aim of the study was to investigate learning style preferences of medical students (2ndyear–5thyear) and compare those styles across years in the medical school (preclinical to clinical).Settings and Design:This study was carried out in the Faculty of Clinical Sciences, College of Health Sciences, Bayero University, Kano, Nigeria. It was a descriptive cross-sectional study.Subjects and Methods:A descriptive cross-sectional study was conducted in Kano, Northwest Nigeria. The Visual, Aural, Read/Write, and Kinesthetic (VARK) questionnaire, a self-administered instrument, was administered to 206 preclinical and clinical years’ medical students in 2016.Statistical Analysis Used:Percentages, proportions, frequency tables, and charts were used in the analysis.Results:The response rate was 87.7%. The mean age of the study sample was 21.9 years. There were 124 (60.2%) males and 82 (39.8%) females. The mean score of each VARK item revealed that kinesthetic, auditory, read/writing, and visual modalities have 6.607 (standard deviation [SD] 2.265), 5.369 (SD 2.436), 4.984 (SD 2.621), and 4.345 (SD 2.468), respectively. The most common preferred learning style for both preclinical and clinical years’ medical students was multimodal learning style.Conclusions:The findings in this study indicate that multimodal learning style is the most preferred, while other preferences are also common. Therefore, this has important implications on how educators deliver teaching and support students’ learning.